Basic calcium phosphate crystals induce the expression of extracellular matrix remodelling enzymes in tenocytes. (9th July 2022) - Chhana, Ashika; Pool, Bregina; Callon, Karen E; Naot, Dorit; Gao, Ryan; Coleman, Brendan; Cornish, Jillian; McCarthy, Geraldine M; Dalbeth, Nicola
Abstract: Objectives: Basic calcium phosphate (BCP) crystals contribute to several syndromes associated with tendon disease, including acute calcific tendinitis and Milwaukee shoulder syndrome. Interactions between BCP crystals and tenocytes (tendon cells) may contribute to these clinical syndromes. This study aimed to determine the direct effects of BCP crystals on tenocyte function and viability. Methods: In vitro assays were used to assess changes in human tenocytes cultured with BCP crystals. Real-time PCR was used to determine changes in the expression of tendon-related genes and extracellular matrix remodelling enzymes (MMPs; a disintegrin and metalloproteases, ADAMTS; and tissue inhibitor of metalloproteinases, TIMPs). ELISA was used to measure protein concentrations in tenocyte supernatants. MTT and alamarBlue™ assays were used to determine changes in cell viability. Results: BCP crystals upregulated tenocyte gene expression of MMP-1, MMP-3, ADAMTS-4 and TIMP-1 after 24 h. Time-course experiments showed expression peaked at 8 h for TIMP-1 and 48 h for MMP-1 and ADAMTS-4. Cyclooxygenase ( COX )- 1 gene expression was upregulated after 48 h. Tenocytes did not alter expression of scleraxis and tendon collagens, and expression of pro-inflammatory cytokines was not induced with BCP crystals. BCP crystals increased tenocyte release of prostaglandin E2 (PGE2 ) and MMP-1 protein after 24 h. However, neither COX-1 inhibition nor COX-2 inhibition led to consistent change in BCP crystal-induced tenocyte gene expression of extracellular matrix remodelling enzymes. BCP crystals had no effect on tenocyte viability. Conclusion: BCP crystals induce extracellular matrix remodelling enzymes, but not inflammatory cytokines, in tenocytes.